1999
DOI: 10.1111/j.1750-3639.1999.tb00219.x
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Synaptic Density is Reduced in Mild to Moderate Human Immunodeficiency Virus Neurocognitive Disorder

Abstract: Dendritic and synaptic damage (without frank neuronal loss) may be seen in milder human immunodeficiency virus (HIV)‐related cognitive disorders. Synapse volume estimates, performed by stereological methods, could enhance the ability to detect subtle neuronal changes that may accompany cognitive impairment in HIV infection. For the present study, synaptic density and neuronal number were assessed by combined stereology/confocal microscopy and these measures were then correlated with ante‐mortem levels of cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
163
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(183 citation statements)
references
References 33 publications
13
163
1
Order By: Relevance
“…44,45 In contrast, increased numbers of microglia, 44 elevated TNF-a mRNA in microglia and astrocytes, 46 evidence of excitotoxins, [47][48][49] decreased synaptic and dendritic density, 45,50 and selective neuronal loss 51,52 constitute the pathologic features most closely associated with the clinical signs of HAD. Furthermore, signs of neuronal apoptosis have been linked to HAD, [53][54][55] although this finding is not clearly associated with viral burden 53 or a history of dementia.…”
Section: Potential Links Between Neuropathology Of Hiv Infection and mentioning
confidence: 99%
“…44,45 In contrast, increased numbers of microglia, 44 elevated TNF-a mRNA in microglia and astrocytes, 46 evidence of excitotoxins, [47][48][49] decreased synaptic and dendritic density, 45,50 and selective neuronal loss 51,52 constitute the pathologic features most closely associated with the clinical signs of HAD. Furthermore, signs of neuronal apoptosis have been linked to HAD, [53][54][55] although this finding is not clearly associated with viral burden 53 or a history of dementia.…”
Section: Potential Links Between Neuropathology Of Hiv Infection and mentioning
confidence: 99%
“…Patients with Axis II disorders were not excluded, however, as this would reduce the subject pool significantly, limiting the feasibility of recruiting a sufficient number of patients. Also, given that AIDS has adverse effects on neurocognitive function, those known to be infected (as per LRCA records) were excluded (Everall et al, 1999).…”
Section: Participantsmentioning
confidence: 99%
“…Although the incidence of HAD has decreased from an estimated 30% to ~10% in the era of HAART, it remains a significant complication of HIV-1 infection as patients with acquired immunodeficiency syndrome (AIDS) live longer, antiretroviral drugs remain unable to effectively cross the blood brain barrier, and HIV-1 resistance grows due to viral strain mutation. It is widely believed HAD cognitive impairments are associated with the number of immune competent and HIV-1-infected MP (Glass et al 1995), diminished synaptic and dendritic density Everall et al 1999), and selective neuronal loss (Masliah et al 1992;Fox et al 1997). However, not all HAD patients exhibit profound neuronal loss (Seilhean et al 1993) and improvements in cognitive function have been observed after HAART (Ferrando et al 1998;Gendelman et al 1998;Tozzi et al 1999;Robertson et al 2004).…”
Section: Introductionmentioning
confidence: 99%